УЛОГАТА НА ОБУКИТЕ ВО СТЕКНУВАЊЕ ГО НА КОМПЕТЕНЦИИ ЗА ПОМАГАТЕЛНA ДЕЈНОСТ (Annual of the Faculty of Philosophy in Skopje, 2008)
The lack of information concerning the social skills at students from helping professions (psychologists, social workers, pedagogues and special educators) is a very big problem. Students, as future experts in the helping professions, have to communicate appropriately with the people, community and social services and institutions for being successful in their job and relations with their clients.The results from the focus groups and data from the tree questionnaires are showing that the quality and the quantity of the educations during the studies are significant factor in building competences for psychosocial work.The obtained results can not be generalized to all helping professions because of the sample limitation, but they are significant for seeing the current state in regards of the researched characteristics and building a strategy for their improvement in the future experts in helping professions. At the same time, the results present a significant indicator that confirms the idea of redesigning the current study programs that would provide opportunities for the present students to get the needed competencies for providing their professional success.
Keywords: SOCIAL SKILLS; HELPING PROFESSIONS; QUALITY OF EDUCATIONS; QUANTITY OF THE EDUCATIONS